PERFORMANCE ANALYSIS OF ROUTING PROTOCOLS IN LARGE-SCALE COMPUTER NETWORKS USING SIMULATION METHOD - Hafidzun Alim; Arafat Febriandirza (Program Studi Teknik Informatika Universitas Khairun, 2026)
Routing protocols are essential components in computer networks that function to determine the best path in the data transmission process. In large scale networks the selection of the appropriate routing protocol highly influences the Quality of Service or QoS and network stability. This research aims to analyze and compare the performance of OSPF, EIGRP and BGP routing protocols based on QoS parameters which include throughput, delay, jitter and packet loss also convergence time and system resource utilization. The research method used is network simulation using Network Simulator 3 (NS-3) with a quantitative experimental approach. Testing is conducted on a large-scale network with variations in the number of nodes, data traffic patterns, and network topologies. The simulation result data is analyzed to determine the performance differences of each routing protocol. The research results indicate that OSPF has the most optimal performance in large-scale internal networks with high throughput, low latency, and fast convergence time. EIGRP demonstrates stable and balanced performance, while BGP excels in the scalability aspect but has higher convergence time and latency. The conclusion of this research asserts that the selection of routing protocols must be adjusted to the needs and characteristics of the applied network.